Assisting Toddler Health Cadres in Preventing and Handling Stunting by Providing Locally Processed Foods: Pendampingan Kader Kesehatan Balita Dalam Pencegahan Dan Penanganan Stunting Dengan Pemberian Makanan Olahan Lokal - Rahayu Sumaningsih; Teta Puji Rahayu; Sherly Juniawati; Petrus Brammonsas Agustino (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Stunting is a growth disorder in children. A child's height is lower or shorter than the standard for their age. The cause is multifactorial, children do not receive the right amount of nutritious intake for a long time. The incidence of stunting in Puntukdoro Village, Plaosan District, Magetan is two very short children and 10 short children. This activity aims to demonstrate the provision of processed egg food to stunted toddlers, evaluate the height and weight of toddlers after being given locally processed food, and measure the level of knowledge before and after stunting counseling. The implementation method uses a pre-experimental model with a One Group Pretest-Postest. The activity was carried out by providing intervention, counseling, and demonstrating local food processing. Before and after the intervention, pre- and post-tests were tested using a paired t-test. The results of the activity show that the age characteristics of the cadres are mostly over 35 years old (11 people), the most education is at the elementary and junior high school level (14 people, 70%). The increase in knowledge of health cadres was measured by 120 points (pretest points 1830 - average 91.9, post-test points 1950 - average 97.5). Providing counseling and demonstrations of local food processing was able to improve the knowledge of health cadres regarding stunted toddlers in Puntukdoro Village, Plaosan District, Magetan Regency.